Quantifying cognitive-motor interference in virtual reality training after stroke: the role of interfaces - Vourvopoulos, A. (2022)
Globally, stroke is the second leading cause of death above the age of 60 years, with the actual number of strokes to increase because of the ageing population. Stroke results into chronic conditions, loss of independence, affecting both the families of stroke survivors but also public health systems. Virtual Reality (VR) for rehabilitation is considered a novel and effective low-cost approach to re-train motor and cognitive function through strictly defined training tasks in a safe simulated environment. However, little is known about how the choice of VR interfacing technology affects motor and cognitive performance, or what the most cost-effective rehabilitation approach for patients with different prognostics is. In this paper we assessed the effect of four different interfaces in the training of the motor and cognitive domains within a VR neurorehabilitation task. In this study we have evaluated the effect of training using 2-dimensional and 3-dimensional as well as traditional and natural user interfaces with both stroke survivors and healthy participants. Results indicate that 3-dimensional interfaces contribute towards better results in the motor domain at the cost of lower performance in the cognitive domain, suggesting the use 2-dimensional natural user interfaces as a trade-off. Our results provide useful pointers for future directions towards a cost-effective and meaningful interaction in virtual rehabilitation tasks in both motor and cognitive domains.